The use and abuse of the 'model farmer' approach in agricultural extension in Ethiopia. Issue 5 (19th October 2020) - Hailemichael, Selam; Haug, Ruth
ABSTRACT: Purpose: The article examines the implementation and effects of the model farmer-based approach of farmer-to-farmer extension delivery that is in use in Ethiopia. Methodology: The study used mixed methods, combining focus group discussions, key informant interviews, and a household survey. Findings: The model farmer approach has increased extension coverage, improved the possibility for information and technology dissemination, and enabled the inclusion of virtually all farming households in extension and advisory networks. Simultaneously, the approach has become a mechanism for the top-down control of farmers, for the identification and favouritism of better-off farmers, and those with political commitments. Practical implications: The findings show that there is a need to critically reflect on who model farmers are, how they are selected, what their historical and current roles and impact have been, as well as follower farmers' feedback on the approach in order to avoid perpetuating the misuse of the approach. Theoretical implications: The article argues that the Ethiopian context that rewards rapid increase in production and productivity, modernisation of agriculture, competitive commercialisation, and a context that allows the continued entanglement of extension delivery with politics have enabled such misuse of the approach to proliferate. The article questions the extent of applicability of the core farmer-to-farmer extension principles that relate to social ties, reciprocity, collaboration, and minimal social hierarchies in such a context. Originality/value: The study generates important insights about the effects of model farmer-based extension approach, its political dimensions, and the importance of context for successful farmer-to-farmer extension.